Versatile Tri(pyrazolyl)phosphanes as Phosphorus Precursors for the Synthesis of Highly Emitting InP/ZnS Quantum Dots. Issue 46 (17th October 2017) - Panzer, René; Guhrenz, Chris; Haubold, Danny; Hübner, René; Gaponik, Nikolai; Eychmüller, Alexander; Weigand, Jan J.
Abstract: Tri(pyrazolyl)phosphanes (5 R1, R2 ) are utilized as an alternative, cheap and low‐toxic phosphorus source for the convenient synthesis of InP/ZnS quantum dots (QDs). From these precursors, remarkably long‐term stable stock solutions (>6 months) of P(OLA)3 (OLAH=oleylamine) are generated from which the respective pyrazoles are conveniently recovered. P(OLA)3 acts simultaneously as phosphorus source and reducing agent in the synthesis of highly emitting InP/ZnS core/shell QDs. These QDs are characterized by a spectral range between 530–620 nm and photoluminescence quantum yields (PL QYs) between 51–62 %. A proof‐of‐concept white light‐emitting diode (LED) applying the InP/ZnS QDs as a color‐conversion layer was built to demonstrate their applicability and processibility. Abstract : Taking stock : Tri(pyrazolyl)phosphanes are utilized as a less‐toxic P1 source for the synthesis of long‐term stable stock solutions of P(OLA)3 (OLAH=oleylamine). The stock solutions are used for the preparation of InP/ZnS quantum dots emitting in the spectral range between 530–620 nm with photoluminescence quantum yields between 51–62 %. The liberated pyrazoles can easily be recovered and reused.